PENGARUH KOMUNIKASI INTERPERSONAL TENAGA PENDIDIK TERHADAP KEBERHASILAN BELAJAR SISWA MADRASAH ALIYAH KECAMATAN CEMPAKA KOTA BANJARBARU - M. Ropiani; M. Ma'ruf Abdullah; Sanusi sanusi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2015)
Teachers as professionals in the field of education, in addition to understand the things that are philosophical and conceptual, also need to know and carry out the things that are technical. Matters of a technical nature, particularly the activities of managing and implementing the teaching and learning interactions. This research is a quantitative research that emphasizes the analysis of numerical data (numbers) are processed with statistical methods. The method used in this study is a random sampling with Slovin formula. Number of sample are 44 student as respondent. The study found there is a partial effect significant Interpersonal Communication Between Teachers with Learning Results students of class XI in Madrasah Aliyah in District Cempaka  , between teaching and learning activities to the success of Learning, the facilities of the success of the Student class XI studied at Madrasah Aliyah in District Cempaka , There is a simultaneous influence of Interpersonal Communication Between Teachers and Learning Facilities basis for success Student Madrasah Aliyah class XI in District Cempaka. Key words: Interpersonal Communication, Educator, Student Madrasah Aliyah.